Development and fabrication of piezoresistive microcantilever-based glucose biosensor / Nina Korlina Madzhi - Madzhi, Nina Korlina (Institute of Graduate Studies, UiTM, 2012)
This thesis is focused on the Development and Fabrication of the Piezoresistive Microcantilever-based Glucose Biosensor. The objective of this work is to design via simulation a piezoresistive microcantilever sensor suitable for glucose sensing. Then, the piezoresistive microcantilever is fabricated with CMOS micromachining technique. The fabricated piezoresistive microcantilever performed the fabrication process characterization to prove the viability of the design. Finally, the objective in this work is to identify suitable Glucose immobilization technique onto microcantilever surface. The methodology of this work starts with the designing of piezoresistive microcantilever. The microcantilever beam length is selected at 195μm and width, 70μm. On this microcantilever beam there are four different piezoresistor with the length of 80μm, 110μm, 140μm and 170μm. The sacrificial layer of BPSG material in the piezoresistive microcantilever have two different thickness of 0.9μm and 1.8μm.